ANALISIS GAYA BAHASA RETORIS DALAM PIDATO BUNG KARNO - Mina Syanti Lubis (Institut Pendidikan Tapanuli Selatan, 2017)
The purpose of speech is not only give information to the public verbally but speech should pay attention language, diction, and style that used so that the information can be received by audience. the style of language is one of the things taht need to be considered in giving speech because the beauty in using style of language is a hallmark of a good speech. Ir. Soekarto (the firs president of indonesia) was a capable rhetorical to build and burn the spirit of Indonesian youth to be independent and irrespective of the other colonies of the nations. Nationalism, the burning spirit of the youth, an the maintenance of the nation